2020
DOI: 10.3390/rs12030522
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Use of Radar and Optical Satellite Data for Improved Monsoon Cropland Mapping in India

Abstract: Monsoon crops play a critical role in Indian agriculture, hence, monitoring these crops is vital for supporting economic growth and food security for the country. However, monitoring these crops is challenging due to limited availability of optical satellite data due to cloud cover during crop growth stages, landscape heterogeneity, and small field sizes. In this paper, our objective is to develop a robust methodology for high-resolution (10 m) monsoon cropland mapping appropriate for different agro-ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…case of the TIP region. In India, Qadir and Mondal [42] found that the combination of SAR and optical data improves the monsoon cropland detection with an OA = 93%.…”
Section: Discussionmentioning
confidence: 99%
“…case of the TIP region. In India, Qadir and Mondal [42] found that the combination of SAR and optical data improves the monsoon cropland detection with an OA = 93%.…”
Section: Discussionmentioning
confidence: 99%
“…Visual interpretation of reference imagery was based on elements that help to identify land cover features such as location, size, shape, tone, color, shadow, texture, and pattern. A similar procedure was used by [74,75].…”
Section: Training and Validation Samples Collectionmentioning
confidence: 99%
“…Acquiring multiple cloudless S-2 images over a large area is difficult, so many researchers perform analyzes on combinations of a different number of images. In such approaches it is efficient to use cloud computing using ML methods, e.g., Google Earth Engine (some accuracy values reported by the authors: RF = 93.3% [12], SV Mmodi f ied = 98.07% [13], RF = 93% [14]).…”
Section: Introductionmentioning
confidence: 99%